Differential effects of agraz (vaccinium meridionale swartz) consumption in overweight and obese women with metabolic syndrome (2020)
ABSTRACT: Obesity implies higher cardiovascular risk (CVR) than overweight. Polyphenol-rich fruits have shown to ameliorate CVR factors (CVRF). It is not clear whether differential effects could be observed between obese and overweight people consuming these fruits. Objective: To evaluate the effects of agraz on CVRF in overweight and obese women with metabolic syndrome (MetS). Methods: Overweight (n=22) and obese (n=18) women (25-60 years) with MetS, were included in this crossover, double-blind and placebo-controlled study. They consumed agraz or placebo over 4-weeks separated by a 4-wk washout period. At the end of each period, the following parameters were measured: anthropometrics, blood pressure, serum lipid profile, glucose, insulin, adipokines, apolipoprotein (apo)-A1, high sensitivity C-reactive protein (hs-CRP), serum total antioxidant capacity (TAC), endogenous antioxidant enzymes and oxidative stress (OxS) markers. Results: Compared to placebo, agraz consumption significantly (p<0.05) reduced hs-CRP and urinary 8-hydroxy 2 deoxyguanosine (8-OHdG) levels in overweight and obese women, respectively. In both groups, changes in antioxidant markers were significant (p<0.05) and negatively correlated with changes in CVR factors and OxS markers, respectively. Positive correlations were observed with cardioprotective markers. Conclusions: Agraz consumption had differential effects in overweight and obese women, with better effects on inflammation and OxS markers, respectively. Further studies should consider these differential responses when analyzing the results of an intervention, and eventually adjust to get better outcomes.